2015
DOI: 10.1002/2014jd022867
|View full text |Cite
|
Sign up to set email alerts
|

Approximate expressions for lightning electromagnetic fields at near and far ranges: Influence of return‐stroke speed

Abstract: The waveforms of lightning return-stroke electromagnetic fields on ground are studied using the transmission line model. Approximate expressions to calculate lightning electromagnetic fields at near and far ranges are presented. It is found that the waveforms of lightning electric and magnetic fields in the time domain at both near and far ranges can be expressed approximately as the channel-base current waveform multiplied by a factor which is a function of the return-stroke speed v and the horizontal distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…According to the transmission line (TL) model, the peak current of each return stroke can be estimated using the field‐to‐current conversion equation I = (2 πε 0 c 2 DE )/ v [ Mallick et al ., ; Chen et al ., ], where I is the peak current, ε 0 is the permittivity of free space, c is the speed of light, D is the distance from the observation site to the lightning channel, E is the initial amplitude of electric field change [ Lin et al ., ], and ν is the return stroke speed. Rakov [] reported that the negative return stroke speed within the bottom 100 m of channel or so is between c /3 and 2 c /3.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…According to the transmission line (TL) model, the peak current of each return stroke can be estimated using the field‐to‐current conversion equation I = (2 πε 0 c 2 DE )/ v [ Mallick et al ., ; Chen et al ., ], where I is the peak current, ε 0 is the permittivity of free space, c is the speed of light, D is the distance from the observation site to the lightning channel, E is the initial amplitude of electric field change [ Lin et al ., ], and ν is the return stroke speed. Rakov [] reported that the negative return stroke speed within the bottom 100 m of channel or so is between c /3 and 2 c /3.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…It can also be seen from Equation 4, with the increase of distance R, especially at distances R beyond some tens of kilometers, compared with the electrostatic field (related to R −2 term) and the induction field (related to R −3 term), the radiation field (related to R −1 term) gradually becomes the dominant component of the total electromagnetic field generated by the lightning RS (Y. Chen et al, 2015;Uman et al, 1975), and the effect of electrostatic and induction terms is gradually weakened, even negligible (Rachidi et al, 2002).…”
Section: Influence On Different E-field Componentsmentioning
confidence: 95%
“…Thottappillil et al (2001) summarized the analytic expression to show the relationship between the lightning channel current and the electromagnetic radiation. Many following efforts also focused on the research of lightning strokes with high currents and powerful electromagnetic radiation based on the transmission line (TL) model using modified channel-current expressions (Chen et al, 2015;Diendorfer & Uman, 1990;Rachidi & Thottappillil, 1993;Thottappillil et al, 2001;Wang et al, 2018;Willett et al, 1988). Since the magnetic field pulse is launched by the lightning current and can be measured at a long distance, its measurement can provide a means for remotely acquiring the source current waveform.…”
mentioning
confidence: 99%